BRIDGING HUMAN, ANIMAL, AND ENVIRONMENTAL HEALTH FOR SUSTAINABLE DISEASE CONTROL IN WEST AFRICA - Bobadoye, Ayodotun; Aluko, Olawale Julius (FUDMA JOURNAL OF SCIENCES, 2025)
This study examined the dynamics of zoonotic disease control in West Africa, with a focus on integrating human, animal, and environmental health through the One Health framework. A narrative literature review was employed, synthesizing data from outbreak reports, peer-reviewed studies, and policy documents published between 2000 and 2023. Findings revealed that zoonotic diseases accounted for one-third of public health emergencies in the region between 2001 and 2022, with Lassa fever and Ebola constituting the most critical threats. Lassa fever remained endemic, with 1,615 confirmed cases reported in 2021. The Ebola outbreak between 2013 and 2016 led to 28,652 confirmed cases and 11,325 deaths. Key drivers of disease emergence included deforestation, livestock intensification, wildlife trade, migration, and weak cross-border surveillance. Regional initiatives, such as the Regional One Health Coordination Mechanism, enhanced preparedness but were hampered by fragmented governance, limited workforce capacity, and resource constraints. The findings suggested that sustainable disease control required multisectoral collaboration, climate-sensitive forecasting, and strong community engagement. Embedding One Health within national and regional policies was identified as an urgent priority to strengthen health security, build resilience, and reduce the socio-economic burden of future epidemics.